EPIDEMIOLOGI TERPADU AVIAN INFLUENZA (FLU BURUNG) BERBASIS TINDAKAN KESEHATAN MASYARAKAT DALAM RESPON PANDEMI INFLUENZA - Denas Symond (Andalas University, Faculty of Public Health, 2009)
The term surveillance is used in two rather different ways. First, surveillance can mean the continuous security of the factors that determine the occurrence and distribution of disease and other conditions of ill health The second use of the term refers to a special reporting system which is set u for a particularly important health problem or disease, for example the spread of communicable diseases in an epidemic like Avian Influenza (AI) or ( H5N1 ). Such a surveillance system like AI aim to provide quickly information which can be analyzed to determine frequency and to answer like questions: who, where and when.AI epidemiological surveillance has a number of major steps: (I) to identify and confirm outbreaks to ensure that effective action to control the disease is being taken (2) to investigate diseases by clinics and laboratory (3) to investigate and confirm the cases (4) Data collection and public health consolidation (5) Data analysis (6) Feedback (7) Following step is taken . District health officer (DHO) and District veterinary officer (DVO) can use integrated AI surveillance epidemiological to collect such information to support the management and evaluation health activities to prevent community from AI disease. It can be concluded, DHO and DVO may participate together in and use local reporting and surveillance system to combat AI in community